In vitro comparison of early occlusal enamel caries detection and remineralisation using ICDAS II and diagnodent pen in permanent posterior teeth - Rashid, Mohammed Fadhil (2022)
Dental caries is among the most commonly occurring oral diseases or chronic infection. Various in-vitro studies have been carried out using LF devices which reported excellent reproducibility as an adjunct caries diagnostic option. Duraphat® (5% sodium fluoride) and Tooth Mousse Plus® (casein phosphopeptide-amorphous calcium phosphate fluoride) are among commonly used formulations for achieving remineralization of carious lesions (Cardoso et al., 2014; Nhu et al., 2017). The occlusal carious lesion of 120 extracted teeth were evaluated using ICDAS II and DDPen. Then the process of remineralization was carried out by applying either the Colgate Duraphat® or GC Tooth Mousse Plus®. The remineralized lesions were then re-evaluated using ICDAS II and DDPen before performing sectioning and histological examination. The sensitivity and specificity of ICDAS II and DDPen to detect remineralization was calculated and a comparison with the gold standard histological examination was also performed. ICDAS-II scoring performed for the pre- and post-remineralization revealed highly significant difference for the GC Tooth Mousse Plus® group as compared to the control group and a lesser but significant difference for the Colgate Duraphat® group as compared to control group. DDPen scoring for the pre- and post-remineralization revealed that there was similar but significant difference with the use of Colgate Duraphat® or GC Tooth Mousse Plus®. Different cut-off limits for the DDPen were analysed to determine which range was corresponded closest to the Downer’s histological scores. A value of 0-13 for sound teeth, 14-20 for enamel caries and >21 for dentine caries was identified as the most suitable. The spearman’s rank correlation of ICDAS-II and DDPen with the Downer’s histological score (gold standard) revealed a higher association of DDPen score (.738) as compared to ICDAS-II scores (.430). The Area under the receiver operator characteristics curve (AUROC) value of DDPen score and ICDAS-II were compared corresponding to Downer’s histological classification. The AUROC value at Downer’s level 1 was 0.972 for DDPen score range (0-13) and 0.811 for ICDAS-II code 0. The AUROC value at Downer’s level 2 was 0.894 for DDPen score range (14-20) and 0.667 for ICDAS-II code 1-2. The AUROC value at c 3 was 0.838 for DDPen score range (>21) and 0.721 for ICDAS-II code 3. The study concluded that both ICDAS II and DDPen were able to detect remineralization. The cut-off values for DDPen most suitable for detecting remineralization were determined as 0-13 being sound, 14-20 being enamel caries, and >21 being dentine caries. The DDPen was found more sensitive than ICDAS-II to detect remineralization when compared with the Downers histological scores. This can be of particular interest in pregnant women and children in which unnecessary exposure to ionizing radiations has to be avoided to monitor the progression of early carious lesions.